2009
DOI: 10.1007/s10482-009-9354-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental discrimination and molecular characterization of the extracellular soil DNA fraction

Abstract: We experimentally discriminated and qualitatively-quantitatively characterized the extracellular fraction of a forest soil DNA pool. We sequentially extracted and classified the components of extracellular DNA by its strength of interaction with soil colloids as: (1) extractable in water, free in the extracellular soil environment or adsorbed on soil colloids; and as (2) extractable in alkaline buffer after previous extraction in water, bound on soil colloids. The comparative molecular analysis (fluorometer, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…The latter is a likely explanation because the analyzed eDNA material was amplified by PCR primers an- nealing to all foraminiferal sequences (Lecroq et al, 2011). During the PCR, the DNA of planktonic foraminifera might well be outcompeted by the autochthonous DNA of benthic foraminifera, which is potentially more abundant, less damaged and more easily extracted from cells than when tightly absorbed to sediment particles (Ceccherini et al, 2009;Torti et al, 2015). It is noteworthy that the relative proportion of sequence reads may reflect the relative proportion of DNA molecules -but not necessarily that of cells -as shown in the case of a mock foraminiferal DNA community amplified using foraminiferal-specific primers (Esling et al, 2015) Consistent with earlier studies (Capo et al, 2015;Lejzerowicz et al, 2013;Pawłowska et al, 2014;Pedersen et al, 2013), the taxonomic diversity revealed by the analyzed eDNA barcodes overlaps only partly with the diversity based on fossils present in the sediment.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a likely explanation because the analyzed eDNA material was amplified by PCR primers an- nealing to all foraminiferal sequences (Lecroq et al, 2011). During the PCR, the DNA of planktonic foraminifera might well be outcompeted by the autochthonous DNA of benthic foraminifera, which is potentially more abundant, less damaged and more easily extracted from cells than when tightly absorbed to sediment particles (Ceccherini et al, 2009;Torti et al, 2015). It is noteworthy that the relative proportion of sequence reads may reflect the relative proportion of DNA molecules -but not necessarily that of cells -as shown in the case of a mock foraminiferal DNA community amplified using foraminiferal-specific primers (Esling et al, 2015) Consistent with earlier studies (Capo et al, 2015;Lejzerowicz et al, 2013;Pawłowska et al, 2014;Pedersen et al, 2013), the taxonomic diversity revealed by the analyzed eDNA barcodes overlaps only partly with the diversity based on fossils present in the sediment.…”
Section: Discussionmentioning
confidence: 99%
“…As extracellular microbial DNA is likely to be released in close proximity to clay particles (Miltner et al, 2012) or within macro-or microaggregates (Blaud et al, 2012), it may be even more protected than laboratory studies using additions of pure DNA or bacterial inoculum would otherwise suggest (Schimel and Schaeffer, 2012). Although an extensive literature exists to support the stabilization of DNA in soil and sediment (Corinaldesi et al, 2008;Ceccherini et al, 2009;Alawi et al, 2014;Morrissey et al, 2015), this has largely been ignored in DNA based microbial ecology studies.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these problems and prevent a lysis of intact cells, exDNA is desorbed from soil particles via slightly alkaline solutions or phosphate buffers and yielded in the supernatant after centrifugation, avoiding the use of cell-lysing reagents and optionally including DNase inhibitors (e.g. Agnelli et al 2007; Ascher et al 2009b; Ceccherini et al 2009; Ogram et al 1987; Taberlet et al 2012b). Applying such a sequential extraction, next to providing exDNA, increases the total amount of not only extractable soil DNA but also that of iDNA (e.g.…”
Section: Methodological Considerations With Exdna Extractionmentioning
confidence: 99%
“…Bearing additional taxonomic and phylogenetic information with regard to iDNA, exDNA has therefore been used to compare information about microbial communities deriving from both fractions of the total soil DNA pool (Agnelli et al 2004; Ascher et al 2009b; Ceccherini et al 2009; Chroňáková et al 2013; Gómez-Brandón et al 2017b). These studies revealed that some sequences found in the exDNA fraction are not found in the iDNA fraction of the total DNA pool and suggest that they are ancient or so-called relic DNA.…”
Section: Soilmentioning
confidence: 99%